A green microextraction technique using nanomaterials adsorbent as valuable tools for elemental speciation and pharmaceutical contaminants analysis / Nor Suhaila Mohamad Hanapi ... [et al.] - Mohamad Hanapi, Nor Suhaila; Ungku Abdullah, Ungku Amirul Arif; Wan Ibrahim, Wan Nazihah; Mat Hadzir, Nursyamsyila; Zaini, Nurzaimah; Zainal Abidin, Nur Husna (2020)
Recently, substantial great innovations in sample preparation techniques have been focused by many researchers to miniaturize analytical laboratories procedure toward green microextraction techniques. Due to the polluting nature of the conventional sample preparation techniques, micro solid-phase extraction (μ-SPE) was developed as a greener alternative technique. This technique eliminates the lengthy workflow such as precipitation, centrifugation, and filtration which increase the sample preparation time and possible error prior to the instrumental analysis. Various nanomaterial adsorbents such as graphene, carbon nanotubes (CNTs), graphene oxide (GO), alginate graphene oxide (Alg/GO), alginate/CNTs, C18 have been developed and utilized as adsorbent in micro solid phase extraction for enhancing the extraction efficiency of elemental speciation and pharmaceutical contaminants in various matrices. Performance microextraction was evaluated by selected parameters; sample pH, ionic strength, amount of adsorbent, extraction time and desorption conditions. As a result, this technique offers simple approach, rapid analysis and economical value with superior extraction performance efficiencies with regard to sensitivity, selectivity and recovery. It could also be potentially useful for the analysis of elemental speciation and pharmaceutical contaminants analyses.